Small animal Review. (2nd April 2021) - Craig, Mark
Abstract : Summary: In this month's Small Animal Review three published papers relating to animal gut health from other veterinary journals are summarised. The papers for this issue focus on the canine microbiome in gastrointestinal disease and the microbiota-related changes that occur as a result of canine diabetes mellitus, as well as a literature review on the impact of exposure to dietary emulsifiers on bowel and metabolic health.